Contesting Colonial Hegemony: Education, Authority, and Resistance in Gorontalo in the Early 20th Century - Apriyanto, Joni; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri; Rinardi, Haryono (Jurnal Sejarah Citra Lekha, 2025)
This study analyzes the dynamics of educational transformation from a traditional, religion-based system to modern colonial education in Gorontalo in the early twentieth century. The study focuses on the introduction of modern educational models by the Dutch East Indies colonial government and examines how these policies triggered resistance among local elites. Colonial educational transformation affected not only institutional structures but also generated epistemological conflicts, shifts in the authority of knowledge, and broader socio-cultural tensions within Gorontalo society. This study employs a historical method with a qualitative-analytical approach based on colonial archival sources and local materials. The findings show that colonial education was perceived as a hegemonic instrument aimed at producing indigenous bureaucratic elites loyal to colonial interests, while simultaneously threatening the continuity of religious authority, customary values, and the socio-political position of local elites. In this study, local elites primarily refer to religious elites, ulama, religious teachers, and Sufi order leaders, as well as hybrid actors who combined religious authority with administrative roles. Resistance was not expressed through passive rejection but through organized cultural and institutional strategies. From the early twentieth century onward, particularly with the establishment of madrasahs and halaqah in Limboto and Kota Barat in 1923, religious elites pioneered alternative Islamic educational institutions that emphasized Qur’anic studies, Arabic grammar (nahwu–ṣarf), and Islamic history. These institutions were strengthened by broader Islamic intellectual networks linking Gorontalo with Minangkabau and Java. Colonial archival sources also indicate widespread refusal by religious families to enroll their children in government schools.